The Contractile Function of Ventricular Cardiomyocytes Is More Sensitive to Acute 17β-Estradiol Treatment Compared to Atrial Cardiomyocytes - Tatiana A. Myachina; Xenia A. Butova; Raisa A. Simonova; Denis A. Volzhaninov; Anastasia M. Kochurova; Galina V. Kopylova; Daniil V. Shchepkin; Anastasia D. Khokhlova (Cells)
17β-estradiol (E2) is the most active metabolite of estrogen with a wide range of physiological action on cardiac muscle. Previous studies have reported E2 effects predominantly for the ventricles, while the E2 impact on the atria has been less examined. In this study, we focused on the direct E2 effects on atrial and ventricular contractility at the cellular and molecular levels. Single atrial and ventricular cardiomyocytes (CM) from adult (24 weeks-old) female Wistar rats were incubated with 10 nM E2 for 15 min. Sarcomere length and cytosolic [Ca2+]i transients were measured in mechanically non-loaded CM, and the tension–length relationship was studied in CM mechanically loaded by carbon fibers. The actin–myosin interaction and sarcomeric protein phosphorylation were analyzed using an in vitro motility assay and gel electrophoresis with Pro-Q Diamond phosphoprotein stain. E2 had chamber-specific effects on the contractile function of CM with a pronounced influence on ventricular CM. The characteristics of [Ca2+]i transients did not change in both atrial and ventricular CM. However, in ventricular CM, E2 reduced the amplitude and maximum velocity of sarcomere shortening and decreased the slope of the passive tension–length relationship that was associated with increased TnI and cMyBP-C phosphorylation. E2 treatment accelerated the cross-bridge cycle of both atrial and ventricular myosin that was associated with increased phosphorylation of the myosin essential light chain. This study shows that E2 impairs the mechanical function of the ventricular myocardium while atrial contractility remains mostly preserved. Hormonal replacement therapy (HRT) with estrogen is by far the most effective therapy for treating climacteric symptoms experienced during menopause. Here we found a chamber specificity of myocardial contractile function to E2 that should be taken into account for the potential side effects of HRT.